2022
DOI: 10.1111/dar.13469
|View full text |Cite
|
Sign up to set email alerts
|

The role of alcohol packaging as a health communications tool: An online cross‐sectional survey and experiment with young adult drinkers in the United Kingdom

Abstract: Introduction Alcohol packaging is a potentially valuable means of communicating product and health‐related information, with growing academic and political interest in its role as a health communications vehicle. Methods An online cross‐sectional survey and experiment were conducted with a non‐probability sample of 18–35‐year‐old drinkers in the United Kingdom (n = 1360). The survey assessed exposure to, and engagement with, current messaging on packs, and support for displaying product and health‐related info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This research expands upon several areas of research, including literature relating to sustainability, extrinsic product cues, cue utilization theory and secondary packaging. Our findings contribute to the literature on beverage packaging styles and formats (Barnett et al, 2016;Jones et al, 2022;Orlowski et al, 2022a;Sugrue and Dando, 2018), specifically as it pertains to craft beer, as it is the first to explore consumer perceptions of secondary packaging for beverage products. Additionally, while most food and beverage packaging studies of primary packaging have generally found that packaging influences purchasing decisions through mechanisms such as taste and quality perceptions (Steenis et al, 2017;Wang, 2013), our research expands on this linkage to include perceptions of sustainable packaging and packaging innovation.…”
Section: Academic Implicationsmentioning
confidence: 77%
“…This research expands upon several areas of research, including literature relating to sustainability, extrinsic product cues, cue utilization theory and secondary packaging. Our findings contribute to the literature on beverage packaging styles and formats (Barnett et al, 2016;Jones et al, 2022;Orlowski et al, 2022a;Sugrue and Dando, 2018), specifically as it pertains to craft beer, as it is the first to explore consumer perceptions of secondary packaging for beverage products. Additionally, while most food and beverage packaging studies of primary packaging have generally found that packaging influences purchasing decisions through mechanisms such as taste and quality perceptions (Steenis et al, 2017;Wang, 2013), our research expands on this linkage to include perceptions of sustainable packaging and packaging innovation.…”
Section: Academic Implicationsmentioning
confidence: 77%
“…Second, recent evidence reviews have provided recommendations for increasing the effectiveness of alcohol warnings in general [25][26][27], but there is ongoing debate surrounding which warning contents and formats are most effective in targeting young people. Some research has concluded that exposure to alcohol warnings reduces the appeal and social acceptability of alcohol products [28] and significantly increases knowledge about alcohol-related risks among the youth segment [29], whereas other studies have found that alcohol warnings tended to elicit negative and "on-the-defensive" reactions in young people that could prove to be counterproductive or even increase binge-drinking behaviors [21,30]. Some studies have shown that messages featuring short-term (rather than long-term) alcohol risks raise greater awareness of the harms of alcohol among young people [31] because young people feel particularly concerned by short-term risk warnings [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that a similar approach to adding cancer warning labels to alcohol containers would raise risk awareness and decrease alcohol consumption. Indeed, recent studies have demonstrated that cancer warning labels can improve knowledge about the alcohol-cancer link, increase risk perceptions, and decrease the selection of alcoholic versus non-alcoholic drinks (Clarke et al, 2021;Jones et al, 2022;Morgenstern et al, 2021). Furthermore, awareness of the alcohol-cancer link predicts stronger support for cancer warning labels (Seidenberg et al, 2022).However, research also suggests that the effectiveness of cancer warning labels may depend on the label design.…”
mentioning
confidence: 99%